Probiotic and technological properties of Lactobacillus spp. strains from the human stomach in the search for potential candidates against gastric microbial dysbiosis - Delgado, Susana; Leite, Analy M. O.; Ruas-Madiedo, Patricia; Mayo, Baltasar (Frontiers in Microbiology, 2015)
This work characterizes a set of lactobacilli strains isolated from the stomach of healthy humans that might serve as probiotic cultures. Ten different strains were recognized by rep-PCR and PFGE fingerprinting among 19 isolates from gastric biopsies and stomach juice samples. These strains belonged to five species, Lactobacillus gasseri (3), Lactobacillus reuteri (2), Lactobacillus vaginalis (2), Lactobacillus fermentum (2) and Lactobacillus casei (1). All ten strains were subjected to a series of in vitro tests to assess their functional and technological properties, including acid resistance, bile tolerance, adhesion to epithelial gastric cells, production of antimicrobial compounds, inhibition of Helicobacter pylori, antioxidative activity, antibiotic resistance, carbohydrate fermentation, glycosidic activities, and ability to grow in milk. As expected, given their origin, all strains showed good resistance to low pH (3.0), with small reductions in counts after 90 min exposition to this pH. Species- and strain-specific differences were detected in terms of the production of antimicrobials, antagonistic effects towards H. pylori, antioxidative activity and adhesion to gastric epithelial cells. None of the strains showed atypical resistance to a series of 16 antibiotics of clinical and veterinary importance. Two L. reuteri strains were deemed as the most appropriate candidates to be used as potential probiotics against microbial gastric disorders; these showed good survival under gastrointestinal conditions reproduced in vitro, along with strong anti-Helicobacter and antioxidative activities. The two L. reuteri strains further displayed appropriated technological traits for their inclusion as adjunct functional cultures in fermented dairy products.